An investigation on the suitability of micro-computed tomography as a non-destructive technique to assess the morphology of laser sintered nylon 12 parts. (December 2014) - Rouholamin, Davood; Hopkinson, Neil
This research study investigates the suitability of micro-computed tomography as a non-destructive technique to assess the morphology of nylon 12 parts manufactured using laser sintering. Density measurements and morphological and mechanical characterisations were performed on sintered nylon 12 parts to measure density and morphological and mechanical properties of the parts. The effects of various levels of laser power on the density, morphological parameters and mechanical properties were investigated and compared. The results show that micro-computed tomography can be used to measure the porosity and pore size of the sintered parts. Micro-computed tomography images provide an understanding of the changes in the three-dimensional structure of the parts. There is no evident change in the porosity or pore size of the laser sintered parts with the increase in laser power. The results of the tensile tests show that the changes applied in laser power had no apparent effect on the ultimate tensile strength and Young's modulus of the laser sintered parts. However, the elongation at break for the parts generally increases as the level of laser power increases. A relationship between non-destructive micro-computed tomography and destructive tensile test results is shown.